TINJAUAN YURIDIS TERHADAP EKSISTENSI LEMBAGA OMBUDSMAN REPUBLIK INDONESIA PERWAKILAN RIAU DALAM PELAKSANAAN FUNGSI PENGAWASAN UNTUK MEWUJUDKAN PEMERINTAHAN YANG BAIK DI PROVINSI RIAU - Susanto, Muhammad Imam; Hb, Gusliana; Ghafur, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Characteristic of a democratic state of law, among others, is a guarantee for any person to bring an action or state governments who did or considered doing a disservice either material or immaterial. Through Law 37 of 2008 on the Ombudsman of the Republic of Indonesia, now Indonesia has had the Ombudsman, the Ombudsman called the Republic of Indonesia, which has strengthened the position and authority. In reality, at this time the function of this agency to oversee the implementation of public service less visible benefits. Society often complained about the poor public services like this. This causes that the existence of the Ombudsman less perceived by the public and cannot meet the needs of the community as a means of complaint to the public service. In addition, the output of the Ombudsman is only a recommendation which has no binding sanctions for public service agencies to implement the recommendations that have not been able to be a solution to realize the reform bureaucracy. The purpose of this thesis, namely: First, determine the existence of the Ombudsman of the Republic of Indonesia Riau Representative in the implementation of the oversight function. Second, find the efforts made by the Ombudsman of the Republic of Indonesia Riau representative in overcoming obstacles. Third, find the constraints faced by the existence of the Ombudsman of the Republic of Indonesia Riau Representative in the implementation of the oversight function to achieve good governance in the province of RiauKey word: law, banking, conventional, syariah.